ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEBERHASILAN TURNAROUND PADA PERUSAHAAN YANG MENGALAMI FINANCIAL DISTRESS DI INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2011 - 2015 - Maria Gabriela Theodorus; Yudith Dyah Hapsari (Prosiding Working Papers Series In Management, 2017)
Turnaround is an improvement effort done by management to restore company performance that experiencing financial distress. This study aims to determine the effect of corporate financial performance (Δseverity), firm size and free assets on the success of company turnaround. Discriminant analysis is used to determine company that experiencing financial distress. Logistic regression analysis is used to determine the factors that influencing the success of company turnaround. Data are from companies in food and beverage industry listed in Indonesia Stock Exchange (IDX) during 2011 – 2015. The results showed that the company’s financial performance (severity) that has positive influence isn’t significant to the success of corporate turnaround and firm size and free assets that have negative influence isn’t necessarily significant to the success of company turnaround.Keywords: Financial Distress, Turnaround, Aseverity, Firm size, Free assets